2005
DOI: 10.1242/dev.01892
|View full text |Cite
|
Sign up to set email alerts
|

A dual role of FGF10 in proliferation and coordinated migration of epithelial leading edge cells during mouse eyelid development

Abstract: The development of the eyelid requires coordinated cellular processes of proliferation, cell shape changes, migration and cell death. Mutant mice deficient in the fibroblast growth factor 10 (Fgf10) gene exhibit open-eyelids at birth. To elucidate the roles of FGF10 during eyelid formation, we examined the expression pattern of Fgf10 during eyelid formation and the phenotype of Fgf10-null eyelids in detail. Fgf10 is expressed by mesenchymal cells just beneath the protruding epidermal cells of the nascent eyeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
99
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(105 citation statements)
references
References 40 publications
5
99
1
Order By: Relevance
“…3A,B), indicating a regional heterogeneity of the eyelid anlagen by this stage or a functional difference of these two receptors in eyelid development. As reported previously, epithelial proliferation and subsequent migration leads to eyelid development (Martin and Parkhurst, 2004;Tao et al, 2005). Our findings suggest that LPA/S1P lipids might regulate epithelial migration in mouse eyelid development by binding to LPA 1 and S1P 1-3 receptors.…”
Section: Potential Roles For Multiple Lpa/s1p Receptor Subtypes Durinsupporting
confidence: 84%
“…3A,B), indicating a regional heterogeneity of the eyelid anlagen by this stage or a functional difference of these two receptors in eyelid development. As reported previously, epithelial proliferation and subsequent migration leads to eyelid development (Martin and Parkhurst, 2004;Tao et al, 2005). Our findings suggest that LPA/S1P lipids might regulate epithelial migration in mouse eyelid development by binding to LPA 1 and S1P 1-3 receptors.…”
Section: Potential Roles For Multiple Lpa/s1p Receptor Subtypes Durinsupporting
confidence: 84%
“…Moreover, lamellipodial and filopodial cellular protrusions have been observed emerging from the tips of the neural folds and linking with each other across the midline (Geelen and Langman, 1979). Similar observations have been made in other morphogenetic systems, for example the closing palatal shelves and fusing eyelids, in which membrane specialisations are observed at the sites of incipient adhesion and fusion (Gato et al, 2002;Tao et al, 2005).…”
Section: Introductionsupporting
confidence: 68%
“…The development eyelids were divided into three fine structures, including root region (Figure 3(1) and (2), arrowheads), mesenchyme ( Figure 3AII), and leading edge ( Figure 3II, dotted line). Growth factors such as FGF10 from mesenchyme cells arrived at the leading edge and promoted their proliferation and migration (Tao et al, 2005). Keratinocyte migration was defective in B6-Co mice.…”
Section: Gene Namementioning
confidence: 99%
“…A similar experiment was performed in Rock1 -/-mice, ROCK1 was not required for wound healing in adult skin, which further indicated that eyelid development was a process of temporal and spatial specificity in mice . Necessary factors for eyelid development can be applied to eyelid tissue in vitro in order to study the mechanism of action of these factors in eyelid development (Tao et al, 2005). Eyelid tissue culture in vitro vividly exhibits eyelid development, as well as temporal and spatial specificity, compared to keratinocytes cultured in vitro.…”
Section: Gene Namementioning
confidence: 99%